Cost Evaluation and Analysis Of Occupational Safety And Health (K3) Implementation In The Poleang Central Market Development Project - Janwar, M. Awal Rafli; Makkawaru, Andi; Sufrianto, Sufrianto; Hado, Hado (Universitas Sulawesi Tenggara, 2023)
Occupational Safety and Health (K3) issues in general in Indonesia are often neglected. This is indicated by the still high number of work accidents. This general problem regarding K3 also occurs in construction operations. The construction service sector is one of the sectors most at risk of work accidents. Loss of life, material, money and time are the consequences which of course will directly hinder the implementation of construction projects. Occupational safety and health aims to create conditions that support work comfort for workers. Occupational Health and Safety (K3) is often neglected, because it is considered a waste of time, moreover it costs a lot of money for (K3). Therefore, planning for Occupational Safety and Health Costs in Building Construction Projects is required. The total cost for the construction of the Poleang Central Market in Bombana district is IDR 39,927,000,000. Meanwhile, the cost allocation for the application of occupational safety and health (K3) required in the Development of the Poleang Central Market in Bombana Regency is Rp. 84,150,000.00 (0.211%). Based on observational data obtained in the field, the implementation of occupational safety and health (K3) in the Poleang Central Market development project is generally good